Osseous ingrowth in allogeneic bone blocks applied for vertical bone augmentation: a preclinical randomised controlled study - Möst, Tobias; Frabschka, Johanna; Kesting, Marco Rainer; Schmitt, Christian; Frohwitter, Gesche; Lutz, Rainer; Schlegel, Karl Andreas (Clinical Oral Investigations, 2019)
Objectives: The aim of the present study was the qualitative and quantitative evaluation of osseous graft consolidation using allogeneic bone blocks for vertical bone augmentation in an animal model. Material and methods: Standardised allogeneic and autologous bone blocks were fixed on the frontal skull of 20 adult female pigs and covered with a resorbable collagen membrane. Animals were sacrificed after 2 and 6 months. Specimens were histologically and histomorphometrically analysed focusing on the amount of vital bone, residual bone substitute material and connective tissue. Furthermore, the amount of expression of bone matrix proteins (collagen type I and osteocalcin) and de novo vessel formation (von Willebrand factor) were quantified by immunohistochemistry. Results: Significantly more allogeneic bone blocks failed for both evaluation time points (p < 0.05). Allogeneic blocks showed significantly less vital bone with more connective tissue formation compared to autologous bone blocks. Increased vessel formation could be detected for both evaluation time points in the contact area of autologous bone with local bone. The expression of collagen type I and osteocalcin was significantly lower in the allogeneic bone graft. Conclusions: Allogeneic cancellous bone blocks showed a significantly higher failure rate compared to autologous bone blocks. Allogeneic bone blocks seemed to negatively affect bone formation or negatively influence the host in the long term, and increased connective tissue formation and block loss should be anticipated. Clinical relevance: In order to maintain patient safety and treatment success clinicians should be persuaded to make a conscious choice of the applied biomaterials with regard to their components and structure.
CRIS-Team Scopus Importer:2019-12-27
Keywords: Allogeneic bone block; Animal model; Bone substitutes; Histomorphometry; Immunohistochemistry